TEXT AS STAGE AND TRAUMA AS PERFORMANCE: A STUDY OF MEENA KANDASAMY’S WORKS FROM A THERAPEUTIC PERSPECTIVE - Kuriakose, Sabitha; Mary, D. Lourdu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper explores how text, performance, and trauma intersect in the works of Meena Kandasamy, presenting her fiction as a powerful space where storytelling becomes both performative and therapeutic. Drawing on trauma theory, performance studies, and bibliotherapy, the study reimagines the literary text as a kind of “stage” where lived experiences of violence, resistance, and healing are enacted. Works such as When I Hit You and Exquisite Cadavers are examined as performative narratives that foreground the body not only as a site where trauma is inscribed, but also as a medium through which resistance is expressed, mirroring elements of theatre and visual composition. The paper argues that Kandasamy’s distinctive narrative techniques, fragmentation, repetition, shifting voices, and visual disruptions within the text resemble theatrical and cinematic strategies, turning the act of reading into an immersive, almost performative experience. This quality allows trauma to be externalized while also encouraging a deeper emotional and psychological engagement from readers, aligning closely with the principles of bibliotherapy. In this sense, readers are not passive observers but active participants who witness, interpret, and emotionally respond, leading to moments of empathy, reflection, and even catharsis. Furthermore, the study situates her work within the broader context of visual and performing arts by drawing connections to stagecraft, performance art, and testimonial theatre. The “textual body” in her fiction parallels the performing body, constantly negotiating silence and voice, vulnerability and agency. Ultimately, this paper suggests that Kandasamy’s fiction redefines trauma narratives as therapeutic performances, opening up new possibilities for integrating literary studies with visual and performing arts to better understand trauma and healing.